Assessment of lymphovascular invasion in gastric carcinoma; do they always indicate lymph node metastasis? (Journal of Pathology of Nepal, 2018)
Background: Stomach cancer is one of the leading causes of cancer death. The grading and staging of this cancer plays an important prognostic role. Lymphovascular invasion predicts poor outcome in gastric cancer. Among the others, lymphovascular invasion provides useful information for the clinical management of patients with gastric cancer. Nevertheless, data about lymphovascular invasion in early-stage and in lymph node-positive gastric cancer are lacking. Hence, significance of lymphovascular invasion to metastatic lymph nodes impacting nodal status in gastric cancer has been studied in this study.Materials and methods: This is a retrospective analysis of twenty nine (29) histologically confirmed gastric carcinoma cases received in the department of Pathology at NMCTH dating from October 2014 to September 2016.Results:  There was male preponderance to gastric carcinoma with male to female ratio of 2.2:1. The age varied from 31- 84 years. There were 17 cases (59%) of intestinal type and 11 cases (38%) of diffuse type of gastric carcinoma and 1 case (3%) of adeno-neuroendocrine carcinoma. Microscopic evaluation for depth of invasion showed tumor invasion till the subserosal connective tissue layer (69%) suggesting pT3 stage.  lymphovascular invasion was identified in 21 cases (72%). There was statistically significant correlation (p value 0.01) between   lymphovascular invasion and nodal status (N0) status. Conclusion: Presence of lymphovascular invasion is considered as poor prognostic marker in case of gastric adenocarcinoma. Pathologist have been reporting their presence or absence in each gastrectomy reports related to gastric carcinoma.This study has established a significant relation between presence of lymphovascular invasion and nodal staging of gastric carcinoma.